(untitled) (UNED Research Journal, 2018)
The Cabra Corral reservoir is the main recreational and sport fishing area of northwest Argentina, with a great interest in the preservation of its environmental conditions. From the Arenales river, the Cabra Corral receives organic matter from domestic and industrial effluents, as well as livestock and agricultural activities of the Lerma Valley. To this is added an important contribution of minerals from the Guachipas river. High levels of mercury and cadmium have been found in this body of water. We assess the health conditions of Odonthestes bonariensis of the Cabra Corral reservoir, which are subject to a very high anthropic impact in relation to the populations of the species in another reservoir of the province, such as the Campo Alegre reservoir. We analyzed histopathological markers in white organs in order to establish if there are differences between the two bodies of water. We performed bi-monthly samplings, extracting samples of liver, kidney and gills, which were processed with routine histological techniques. In addition, water samples were analyzed for quality. In the Cabra Corral reservoir, we found a large number of histopathologies, where the liver was the most affected organ, followed by the kidney and, to a lesser extent, the gills. In the Campo Alegre reservoir, we found a lower proportion of histopathologies. Liver and kidney parasites caused by coccidia associated with inflammatory processes are reported in fish population in Cabra Corral area. The identification and evaluation of histopathological markers confirmed that there are marked differences in the health status of O. bonariensis between the two reservoirs.